IMF Research Bulletin - International Monetary Fund (Washington, D.C International Monetary Fund (IMF), 2000)
This quarterly bulletin selectively summarizes key components of research done at the IMF and provides a listing of research documents and other research-related activities, including IMF conferences and seminars
IMF Research Bulletin is a quarterly publication in English
Keywords: International banking; INTERNATIONAL BANKING; IMF; PERIODICALS